Analysis of energy absorptions in drop-weight tear tests of pipeline steel. (July 2016) - Yu, P.S.; Ru, C.Q.
Highlights: Energy absorbed by different regions in DWTT specimen is analyzed. Fracture energy is quantified from the total energy absorption in specimens. Ratios of fracture energy to total energy absorption in DWTT are obtained. Abstract: The energy absorptions of drop-weight tear tests (DWTT) are analyzed using a finite element model based on the cohesive zone model. The parameters in the traction–separation law for the cohesive zone are validated by matching the simulation results to test data of standard specimens of DWTT. Based on the simulations the fracture energy (defined as the adhesion energy plus the plastic energy surrounding the crack tip) is quantified from the total energy absorption in the standard specimen. A ratio of the fracture energy to the total energy absorption for the steady-state crack propagation in the standard specimen is obtained which could be used to estimate the energy-based toughness of pipeline steel based on the measurable total energy absorption in DWTT.